Comparison of mannitol and citric acid cough provocation tests. (October 2019) - Nurmi, Hanna M.; Lätti, Anne M.; Brannan, John D.; Koskela, Heikki O.
Abstract: Rationale: Citric acid has been used as a cough provocation test for decades. However, the methods of administration have not been standardized. Inhaled mannitol is a novel cough provocation test, which has regulatory approval and can be performed utilizing a simple disposable inhaler in a standardized manner. Objective: To compare the mannitol and citric acid cough provocation tests with respect to their ability to identify subjects with chronic cough and their tolerability. Methods: Subjects with chronic cough (n = 36) and controls (n = 25) performed provocation tests with mannitol and citric acid. Both tests were video recorded. Cough sensitivity was expressed as coughs-to-dose ratios (CDR) and the cumulative doses to mannitol or concentration to citric acid evoking 5 coughs (C5). Forced expiratory volume in 1 s (FEV1 ), visual analogue scales (VAS), test completion rates and the total cough frequencies were analysed. Results: Mannitol and citric acid CDR both effectively separated those with cough and the control subjects (AUC 0.847 and 0.803, respectively) as did C5 (AUC 0.823 and 0.763, respectively). There was a good correlation between the cough sensitivity provoked by the two stimuli, either expressed as CDR (r = 0.65, p < 0.001) or C5 (r = 0.53, p = 0.001). Both tests were similarly tolerated in terms of VAS, although more patients discontinued the mannitol test early, primarily due to cough. Conclusions: Mannitol and citric acid tests correlated well, equally identified subjects with chronic cough and their tolerability was similar. The feasibility issues, strict standardisation and regulatory approval may favour mannitol to be used in clinical cough research. Highlights: Citric acid and mannitol similarly separate subjects with chronic cough from control subjects. The cough responses to these stimuli correlate significantly. These two cough provocation tests are similarly tolerated.